Preparation of Politechnic Sultan Mizan Zainal Abidin (PSMZA) Lecturers in Facing The Industrial Revolution Flow 4.0 - Raja Noor Alina Binti Raja Ali; Mastura Binti Ibrahim (Jurnal Konseling dan Pendidikan, 2018)
Technology development can’t be denied a great role and contribution in the life. The world has undergone a technology transition through the first, second and the third revolutions. Every revolutions having its own progress and achievement.  Now, the world will facing the new revolutions of the industrial revolutions 4.0, which is based on the emergence of supercomputer, smart robot, also unmanned vehicle and variety technologies. Industrial Revolution 4.0 also pushed up the mobile applications as a medium in every life and it’s an inevitable transformation. All parties need to be prepared and adapted to face the challenges of the Industrial Revolutions 4.0 to remain competent. This study aims to identify teaching methods for PSMZA lecturers in the face of the challenges of the Industrial Revolutions 4.0. The study was conducted qualitatively in the form of a document evaluation. Some previous reports were reviewed through findings from the conference and journal, identified as a literature review, data were collected and analyzed using a matrix table. Researchers suggested that polytechnic management set the strategy by increasing the training and seminars on the Industrial Revolution 4.0 and taking other effective measures to ensure that lecturers are prepared to take on the challenge. The PSMZA lecturer is advised to increase knowledge in information technology, further reading and training remain competent in the current Industrial Revolution 4.0.